Unexplained acute backache in longstanding ankylosing spondylitis. Issue 6509 (7th December 1985) - Dunn, N; Preston, B; Jones, K L
Abstract : Patients with longstanding ankylosing spondylitis who develop untypical severe backache may have spinal lesions.